The origin and growth of the English constitution;: an historical treatise ... the gradual development of the English constitutional system, and the growth out of that system of the Federal Republic of the United States - Taylor, Hannis (Houghton, Mifflin, 1898)
v. 1. The making of the constitution.--v.2. The after-growth of the constitution.